Overview of Postpartum Mothers' Knowledge of Proper Breastfeeding Techniques through WhatsApp-Based Education in Makassar City - Sri Muliani; Fitria Fitria; Ummul Fadhilah (Jurnal Kesehatan dan Kedokteran, 2026)
Breastfeeding success in the early postpartum period is strongly influenced by mothers’ knowledge of correct breastfeeding techniques, yet education delivered in health facilities is often brief and may not provide sufficient reinforcement. Widely used messaging platforms such as WhatsApp offer an opportunity to deliver flexible, repeatable, and accessible breastfeeding education, particularly in urban settings like Makassar City. Objective: This study aimed to describe postpartum mothers’ knowledge of correct breastfeeding techniques after receiving WhatsApp-based education in Makassar City. Methodology: A quantitative descriptive design with a pretest–posttest format was employed. Forty postpartum mothers were recruited through purposive sampling based on inclusion criteria. Educational materials (text, images, and videos) were delivered via WhatsApp, and knowledge was measured using a structured questionnaire administered before and after the education. Data were analyzed descriptively by comparing pretest and posttest mean scores across four domains: breastfeeding position, latch-on technique, signs of adequate breast milk intake, and management of common breastfeeding problems. Findings: Postpartum mothers’ knowledge increased markedly after the intervention. The mean score rose from 54.10 at pretest to 86.80 at posttest, and all knowledge domains showed consistent improvement. WhatsApp functioned effectively as an educational medium due to its accessibility, flexibility, and capacity to support repeated learning. Implications: WhatsApp-based education can be considered for integration into routine postpartum health services to strengthen breastfeeding literacy and complement facility-based counseling, especially in urban contexts. Originality: This study provides technique-domain–specific evidence on WhatsApp-delivered breastfeeding education among postpartum mothers in an urban Indonesian setting, offering a practical and scalable model for postpartum breastfeeding support.